Naringin Interferes Doxorubicin-Induced Myocardial Injury by Promoting the Expression of ECHS1 - Zhao, Zirui; Yang, Shilei; Deng, Yawen; Wang, Liang; Zhang, Yifen; Feng, Zhenyu; Li, Han; Chi, Zhongchao; Xie, Yunpeng; Dong, Deshi (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) leads to myocardial cell damage and irreversible heart failure, which limits the clinical application of DOX. Naringin has biological functions of inhibiting inflammation, oxidative stress and apoptosis. Our aim was to investigate whether Naringin could prevent DOX-related cardiotoxicity in mice. Naringin was administered by gavage and mice were intraperitoneally injected with doxorubicin (1mg/kg/day) for 15 days. H&E, Masson, TUNEL and others experiments were examined. NRVMs and H9C2 cells were treated with Naringin and DOX in vitro. Using IF, ELISA and Western Blot to detect the effect of Naringin and ECHS1 on cells. The results showed that Naringin could prevent DOX related cardiac injury, inhibit cardiac oxidative stress, inflammation and apoptosis in vivo and in vitro. Inhibition of ECHS1 could interfere the effect of Naringin on DOX-induced myocardial injury. Naringin may provide a new cardiac protective tool for preventing the cardiotoxicity of anthracycline drugs.